Multiply <math><mstyle displaystyle="true"><mi>x</mi></mstyle></math> by <math><mstyle displaystyle="true"><mn>1</mn></mstyle></math> .

Move all terms containing <math><mstyle displaystyle="true"><mi>y</mi></mstyle></math> to the left side of the inequality.

Add <math><mstyle displaystyle="true"><mi>y</mi></mstyle></math> to both sides of the inequality.

Add <math><mstyle displaystyle="true"><mi>y</mi></mstyle></math> and <math><mstyle displaystyle="true"><mi>y</mi></mstyle></math> .

Move all terms not containing <math><mstyle displaystyle="true"><mi>y</mi></mstyle></math> to the right side of the inequality.

Subtract <math><mstyle displaystyle="true"><mi>x</mi></mstyle></math> from both sides of the inequality.

Subtract <math><mstyle displaystyle="true"><mi>x</mi></mstyle></math> from <math><mstyle displaystyle="true"><mi>x</mi></mstyle></math> .

Divide each term by <math><mstyle displaystyle="true"><mn>2</mn></mstyle></math> and simplify.

Divide each term in <math><mstyle displaystyle="true"><mn>2</mn><mi>y</mi><mo><</mo><mn>0</mn></mstyle></math> by <math><mstyle displaystyle="true"><mn>2</mn></mstyle></math> .

Cancel the common factor of <math><mstyle displaystyle="true"><mn>2</mn></mstyle></math> .

Cancel the common factor.

Divide <math><mstyle displaystyle="true"><mi>y</mi></mstyle></math> by <math><mstyle displaystyle="true"><mn>1</mn></mstyle></math> .

Divide <math><mstyle displaystyle="true"><mn>0</mn></mstyle></math> by <math><mstyle displaystyle="true"><mn>2</mn></mstyle></math> .

Multiply <math><mstyle displaystyle="true"><mi>x</mi></mstyle></math> by <math><mstyle displaystyle="true"><mn>1</mn></mstyle></math> .

Subtract <math><mstyle displaystyle="true"><mi>x</mi></mstyle></math> from both sides of the inequality.

Multiply each term in <math><mstyle displaystyle="true"><mo>-</mo><mi>y</mi><mo>></mo><mn>2</mn><mo>-</mo><mi>x</mi></mstyle></math> by <math><mstyle displaystyle="true"><mo>-</mo><mn>1</mn></mstyle></math>

Multiply each term in <math><mstyle displaystyle="true"><mo>-</mo><mi>y</mi><mo>></mo><mn>2</mn><mo>-</mo><mi>x</mi></mstyle></math> by <math><mstyle displaystyle="true"><mo>-</mo><mn>1</mn></mstyle></math> . When multiplying or dividing both sides of an inequality by a negative value, flip the direction of the inequality sign.

Multiply <math><mstyle displaystyle="true"><mrow><mo>(</mo><mo>-</mo><mi>y</mi><mo>)</mo></mrow><mo>⋅</mo><mo>-</mo><mn>1</mn></mstyle></math> .

Multiply <math><mstyle displaystyle="true"><mo>-</mo><mn>1</mn></mstyle></math> by <math><mstyle displaystyle="true"><mo>-</mo><mn>1</mn></mstyle></math> .

Multiply <math><mstyle displaystyle="true"><mi>y</mi></mstyle></math> by <math><mstyle displaystyle="true"><mn>1</mn></mstyle></math> .

Simplify each term.

Multiply <math><mstyle displaystyle="true"><mn>2</mn></mstyle></math> by <math><mstyle displaystyle="true"><mo>-</mo><mn>1</mn></mstyle></math> .

Multiply <math><mstyle displaystyle="true"><mrow><mo>(</mo><mo>-</mo><mi>x</mi><mo>)</mo></mrow><mo>⋅</mo><mo>-</mo><mn>1</mn></mstyle></math> .

Multiply <math><mstyle displaystyle="true"><mo>-</mo><mn>1</mn></mstyle></math> by <math><mstyle displaystyle="true"><mo>-</mo><mn>1</mn></mstyle></math> .

Multiply <math><mstyle displaystyle="true"><mi>x</mi></mstyle></math> by <math><mstyle displaystyle="true"><mn>1</mn></mstyle></math> .

Find the intersection of <math><mstyle displaystyle="true"><mi>y</mi><mo><</mo><mn>0</mn></mstyle></math> and <math><mstyle displaystyle="true"><mi>y</mi><mo><</mo><mo>-</mo><mn>2</mn><mo>+</mo><mi>x</mi></mstyle></math> .

Do you know how to Solve the System of Inequalities x+y<1x-y>2? If not, you can write to our math experts in our application. The best solution for your task you can find above on this page.